1998
DOI: 10.1093/occmed/48.5.329
|View full text |Cite
|
Sign up to set email alerts
|

Life events, mood, mental strain and cardiovascular risk factors in Swedish middle-aged men. Data from the Swedish part of the Renault/Volvo Coeur Study

Abstract: The associations between life events, mood, mental strain and cardiovascular risk factors were investigated in the Renault/Volvo Coeur Study. About 1,000 men, blue-collar and white-collar workers, were asked by means of interview-administered questionnaires about life events experienced during the year preceding the screening, about mood and mental strain and about smoking, alcohol consumption and exercise habits. Blood pressure, concentration of serum lipids and blood glucose, and anthropometric measures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
2
4
0
1
Order By: Relevance
“…Previous studies have shown that the association between weight gain and stress or adverse life events differed between men and women [7,10,22]. In the present study, there were gender differences since women reported a higher impact and slower adaptation to some of the adverse events, and also showed a greater weight change for the same event than men did.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Previous studies have shown that the association between weight gain and stress or adverse life events differed between men and women [7,10,22]. In the present study, there were gender differences since women reported a higher impact and slower adaptation to some of the adverse events, and also showed a greater weight change for the same event than men did.…”
Section: Discussionsupporting
confidence: 40%
“…Differences in reactions to stress leading to variations in impact on body weight may exist between obese and healthy weight adults or between men and women [3-5]. Based on three prospective cohorts, it was shown that the effect of stress on body weight differed according to baseline body mass index (BMI); positive associations were only found among overweight individuals [7-10]. In addition, Harding et al also found differences in the relationships between psychosocial stress including life events and weight change by baseline BMI over a period of five years, emphasizing the role of initial weight status [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posebne stresne obremenitve, pomanjkanje socialne podpore (»trdi ma~izem«) in razdra`ljivost kot znak maskirane depresije so dejavniki tveganja za okvare bio-psihosocialno blagostanja (zdravja), ki se lahko ka`e kot izgorelost (37). Delovni pogoji in neustrezna pri~akovanja (ocena finan~nega stanja (Tabela 2)) lahko oja~ajo nekatere znake PTSM (38), ki praviloma ostajajo prezr ti, in se ka`ejo kot tesnobnost, depresivnost in zloraba alkohola (39).…”
Section: Misijaunclassified
“…Stressful life events, lack of social support and depression are thought to influence risks for poor health status (1,2). On the other hand, social support, disclosure of trauma and social acknowledgement are relevant interpersonal factors in trauma recovery (3,4).…”
Section: Introductionmentioning
confidence: 99%